Anaphylactic reaction to dapsone: case report - Batista da Silva, Lorena; de Queiroz Almeida, Geisa; Beisl Noblat, Antonio Carlos; Silva Amaral, Letícia Maria; Noblat de Carvalho Santos, Glaucia; de Araújo Costa Beisl Noblat, Lúcia (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Dapsone is an antibiotic capable of inhibiting the synthesis of folic acid in bacteria and producing a bacteriostatic effect. Adverse reactions have already been recorded with the use of this medication. The objective of this study was to describe the case of a patient who developed an anaphylactic reaction after administration of dapsone, review the literature on the subject and apply algorithms to assess causality. Anaphylaxis is an im-mediate hypersensitivity reaction that can potentially be fatal. This is the first case report of anaphylactic reaction to dapsone described in the literature based on research carried out by the authors in databases.